2018
DOI: 10.1177/0956797618765477
|View full text |Cite
|
Sign up to set email alerts
|

Two Ways to Facial Expression Recognition? Motor and Visual Information Have Different Effects on Facial Expression Recognition

Abstract: Motor-based theories of facial expression recognition propose that the visual perception of facial expression is aided by sensorimotor processes that are also used for the production of the same expression. Accordingly, sensorimotor and visual processes should provide congruent emotional information about a facial expression. Here, we report evidence that challenges this view. Specifically, the repeated execution of facial expressions has the opposite effect on the recognition of a subsequent facial expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Whereas this might appear to contradict the view that cognition and emotional meaning is grounded in sensorimotor processes, there is research suggesting that facial simulation does not always relate to or occur in emotion processing tasks (e.g., Arnold and Winkielman 2019 ). Various routes to emotion processing have been shown to play a role in detecting and grasping emotional concepts (e.g., Arnold and Winkielman 2019 ; de la Rosa et al 2018 ; Stel 2016 ). In the present study such routes pertain to visual information, auditory information, semantic information as well as previous knowledge on emotion concepts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas this might appear to contradict the view that cognition and emotional meaning is grounded in sensorimotor processes, there is research suggesting that facial simulation does not always relate to or occur in emotion processing tasks (e.g., Arnold and Winkielman 2019 ). Various routes to emotion processing have been shown to play a role in detecting and grasping emotional concepts (e.g., Arnold and Winkielman 2019 ; de la Rosa et al 2018 ; Stel 2016 ). In the present study such routes pertain to visual information, auditory information, semantic information as well as previous knowledge on emotion concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Accurately detecting emotion-related information is an important ability for successful human interaction. Grounded in the embodied cognition view of social information processing (e.g., Arnold and Winkielman 2019 ; Niedenthal 2007 ; Niedenthal et al 2005 ), in numerous emotion processing studies, both written words as well as facial expressions have been shown to trigger a simulation process that sometimes is reflected in facial muscle activity (e.g., Foroni and Semin 2009 ; Niedenthal 2007 ). Especially the simulation of facial expressions involves cortical processing related to motor simulation of facial expressions, the posterior cingulate cortex, and medial temporal lobe structures (Schilbach et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, experimental evidence that newborns and infants mimic others' facial expressions and react to them accordingly with the emotions they convey, seems to contrast with this view; for instance, they react with avoidance and fear to negative expressions long before a sophisticated capacity for ToM has developed (Ruba, Meltzoff, & Repacholi, 2019), suggesting that the potential process underlying understanding others' emotions is more likely based on early, pre-wired mechanisms rather than on high-level cognitive skills (Preston & de Waal, 2002). An alternative mechanism to the ToM proposes that the recognition of others' emotions requires both visual analysis and 'sensorimotor simulation' (de la Rosa, Fademrecht, Bülthoff, Giese, & Curio, 2018;Paracampo, Pirruccio, Costa, Borgomaneri, & Avenanti, 2018) -an unconscious, covert imitation and automatic activation of the sensorimotor programs of the observed facial postures or movements (Goldman & Sripada, 2005;Ipser & Cook, 2016;Montgomery & Haxby, 2008;Niedenthal, Mermillod, Maringer, & Hess, 2010;Paracampo, Tidoni, Borgomaneri, Di Pellegrino, & Avenanti, 2017), suggesting that humans are 'cabled' with a neural mechanism that let them to almost literally resonate with others (Adolphs, 2009;Ferrari, Tramacere, Simpson, & Iriki, 2013;Gallese, 2016). This mechanism, in turn, would activate interconnected systems, including the limbic system, allowing observers to re-enact the others' affective states, and therefore, in last analysis, to understand them (Wood, Rychlowska, Korb, & Niedenthal, 2016;Tramacere, Pievani, & Ferrari, 2017).…”
Section: Introductionmentioning
confidence: 99%